Ulnar Compression Neuropathy Secondary to Ganglion Cyst at the Elbow Joint: A Case Report - Suman Kumar Basnet; Prakash Shrestha; Gaurav Bir Bajracharya (Journal of Nepal Medical Association)
Ulnar neuropathy is a common peripheral neuropathy, with cubital tunnel compression being the second most frequent upper extremity compression syndrome. Ganglion cysts, though rare, can contribute to ulnar nerve compression in the cubital tunnel. Here, we present a case of a 62-year-old farmer with longstanding diabetes and dyslipidemia who experienced progressive pain and numbness in his medial fingers, exacerbated by elbow flexion. Initially misdiagnosed and treated for Hansen’s disease. Clinico-radiological evaluation revealed a multiloculated cystic lesion in the posteromedial aspect of his left elbow, compressing the ulnar nerve. Surgical excision of the ganglion cyst alleviated symptoms, though residual motor deficits persisted postoperatively. This case underscores the importance of considering ganglion cysts in the differential diagnosis of cubital tunnel syndrome, highlighting the diagnostic challenges and therapeutic considerations in managing this rare etiology.